Teaching English grammar for ESP learners: An exploration of content based instruction - Romadhon, Romadhon (Journal of English and Education (JEE), 2024)
This study examined two instructional methods of grammar teaching for polytechnic students: the traditional method of translation and memorization and Content-Based Instruction (CBI). By involving first-year students majoring in Cyber Security, this study measured the impact of each method using pre- and post-tests focusing on key grammar topics integrated into IT content. The results showed that students in the CBI class outperformed those in the conventional class, wherein 53.34% of the former group attained converted grades of A and B while only 26.67% achieved similar grades in the latter. The students’ feedback collected through questionnaires indicated that they preferred CBI because it was more relevant and applicable to reality, thus motivating them and making the grammar understandable in context. CBI was effective in ESP settings because it combined language skills with subject matter, but it necessitated instructors to handle both language teaching and content area. The current study highlighted that CBI could be a more meaningful grammar instruction for providing better learner outcomes in technical fields.